Effects of sewage sludge on the growth and yield of jute (International Journal of Agricultural Research, Innovation and Technology, 2025)
An outdoor research was executed to assess the impact of sewage sludge and inorganic fertilizer on the fertility of soil and yield of jute, utilizing the high-yielding variety of jute (Corchorus olitorius L.) O-9897 as the sample plant. Six treatments of treated sewage sludge (SS) and suggested amounts of chemical fertilizers (RDF) with three replications were as T1: (Control), T2: (SS 5 t ha‑1), T3: (SS 5 t ha‑1 + ½ RDF), T4: (SS 5 t ha‑1 + ¾ RDF), T5: (SS 5 t ha‑1 + ¼ RDF), and T6: RDF. It was found that the treatment T4 (SS + ¾ RDF) as well as T5 (SS + ¼ RDF) had the highest growth and yield of jute, where the plant height, base diameter, fiber yield and stick weight were increased 67.65, 48.28, 60, and 63.49%, respectively in comparison to the control. The maximum amounts of organic matter and zinc were found for treatment T3, whereas nitrogen, phosphorus, potassium and sulfur were also noted as highest in treatment T4. The implementation of sewage sludge alone enhanced jute growth, yield, and soil nutrient levels compared to the control. However, combining sewage sludge with chemical fertilizers produced improved outcomes in boosting the fertility of soil and the yield of jute.Int. J. Agril. Res. Innov. Tech. 15(1): 54-61, June 2025